(3eUGYO GdfXQ ddCTQGa Ydi ebGUO GdShQs - (3GdHbGYj , EHQGgje Hf YeQ Hf MSf GdQHGW Hf Ydj Hf CHj HcQ GdHbGYj GdTGaYj, HQgGf GdOjf CHh GdMSf,J (B885 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi Yde ShQ GdbQBf HeG Od Ydi bGUOgG s
(3BNQgG (B:s
(3hbjd efgG BNQ fRd Ydi QShd Gddg Udi Gddg Ydjg hSde hGJbhG jhekG JQLYhf s
(3fSNI KGdKIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B56 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B71s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA GdGh (B- ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1704s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
Keywords: (3JYHjQ GdQDjGs